Combined impact of lemongrass and spearmint herbs on performance, serum metabolites, liver enzymes, and meat quality of broiler - Rahman, Md Aliar; Sultana, Sabiha; Redoy, Md Rahat Ahmad; Debi, Momota Rani; Chowdhury, Rakhi; Al Mamun, Mohammad (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: This study aimed to assess the influence of feeding fresh lemongrass (Cymbopogon citratus) or spearmint (Mentha spicata) and their combination on performance, serum metabolites, liver enzymes, and meat quality in broilers. Materials and Methods: A total of 168 day-old Indian River chicks were arbitrarily offered four experimental rations: (i) control ration (CT-R): corn-soya-based ration, (ii) lemongrass ration (LGR): CT-R + 1.0% DM of lemongrass; (iii) spearmint ration (SM-R): CT-R + 1.0% DM of spearmint; and (iv) lemongrass-spearmint ration (LS-R): CT-R + 0.5% DM from both lemongrass and spearmint. Each ration was given to 42 birds for a duration of 35 days, with 3 replications and 14 birds each. Results: Elevated body weight gain was observed in LG-R (1,502 gm), LS-R (1,492 gm), and SM-R (1,474 gm) compared to CT-R (1,451 gm) (p = 0.078). Herbal rations successfully reduced almost 3%–5% of serum and meat total cholesterol concentrations compared to CT-R. Compared to CT-R, the highest zinc and iron concentrations of serum and meat were measured in LG-R and SM-R, respectively, while both minerals of serum and meat were observed to be better in LS-R (p < 0.05). Herbal rations significantly improved serum liver enzyme activity and ameliorated the red color of breast and thigh meat but failed to improve the lightness and yellowness of both types of meat compared to CT-R. Conclusions: LG-R, SM-R, and LS-R improved bird performance, liver health, and meat color, and lowered serum and meat cholesterol levels. But among them, LS-R efficaciously increased the serum and meat zinc and iron concentrations. J. Adv. Vet. Anim. Res., 9(4): 712–719, December 2022 http://doi.org/10.5455/javar.2022.i640